Communication Patterns in Intercultural Marriages Involving Muslims - Ilyas, Sanusi; Kobayashi, Riko; Nishida, Daiki (Journal International Dakwah and Communication, 2024)
This study aims to explore communication patterns within intercultural marriages involving Muslim individuals. The increasing globalization and migration have led to a rise in intercultural marriages, often presenting unique challenges, particularly in communication. The study specifically focuses on the experiences of Muslim individuals in such marriages to understand the communication strategies they employ and the factors that influence these patterns. A qualitative approach, involving in-depth interviews with participants from various cultural backgrounds, was adopted to gather rich and detailed data. The findings reveal that effective communication in intercultural marriages involving Muslims is influenced by factors such as cultural differences, religious beliefs, and individual personalities. Participants employed various strategies, including accommodation, compromise, and intercultural mediation, to navigate these complexities. The study contributes to the existing literature on intercultural communication by highlighting the unique dynamics of Muslim intercultural marriages and providing insights for couples, counselors, and researchers.